Structural, optical, and electrical investigation of multilayered MnO2(n)/ NiO(p) heterojunctions for supercapacitors applications - Alanazi, Maha; Ghrib, Taher; Ercan, Filiz; Alsubaie, Mizna; Demirci, Tuna; Kaygili, Omer; Ercan, Ismail (Elsevier, 2023)
Heterojunctions of alternating MnO2 and NiO thin films were deposited on an Indium Tin Oxide (ITO). The MnO2 and NiO thin films were synthesized by electrodeposition and sol-gel methods respectively. The structural morphology of the synthesized heterojunctions was investigated by scanning electron microscopy (SEM) and atomic force microscopy (AFM). The microstructural and chemical compositions were examined by X-ray diffraction (XRD), Fourier transform infrared (FTIR), and Raman techniques. The optical properties were investigated by Ultraviolet-Visible (UV) analysis. The electrical conductivity, specific capacitance, and charge carrier density were determined using the Hall effect and Electrochemical impedance spectroscopy (EIS) methods. As a result, it was found that the MnO2 and NiO thin films crystallize in tetragonal and cubic crystal systems respectively. Increasing the number of NiO/MnO2 heterojunctions increases the electrical conductivity from 9.7 x 10- 7 to 1.2 x 10-3 S.cm- 1, the bandgap decreased 3.16 to 2.62 eV, the volume carrier density rises from 5.17 x 1011 to 4.62 x 1012 cm-3. The specimens constituted of two and four alternative staked MnO2 and NiO layers are characterized by a specific capacitance of 3.6 x 103 and 5.8 x 103 F.g -1 and capacitance retention of 14.8 and 12.9% which consider them promising materials for supercapacitor devices.
Keywords: Heterojunction; MnO2; NiO; Supercapacitor; Specific capacitance